2017
DOI: 10.1002/nur.21838
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analyses of adoptive parents’ expectations and depressive symptoms

Abstract: Grounded in a theoretical model specific to adoptive parents, we examined the relationship between parental expectations and depressive symptoms across time. Assessments of 129 adoptive parents of 64 children were performed at three time points before and after placement of an adopted child with the family: 4–6 weeks pre-placement and 4–6 weeks and 5–6 months post-placement. Expectations were assessed in four dimensions: expectations of self as parents, of the child, of family and friends, and of society. Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…This could be understood as mothers continuously realigning expectations of themselves and their child in response to real experiences of parenting. Foli et al's (2017aFoli et al's ( , 2017b mid-range theory of post-adoption depression helps to explain such changes, suggesting that mothers' levels of depression decrease as alignment between expectation and reality increases. However, our findings indicated that mothers continue to experience NegMH even when expectations of self and child are adjusted, suggesting factors associated with the daily function of adoptive parenting put mothers at risk of NegMH, such as the experience of "extreme parenting.…”
Section: Discussionmentioning
confidence: 99%
“…This could be understood as mothers continuously realigning expectations of themselves and their child in response to real experiences of parenting. Foli et al's (2017aFoli et al's ( , 2017b mid-range theory of post-adoption depression helps to explain such changes, suggesting that mothers' levels of depression decrease as alignment between expectation and reality increases. However, our findings indicated that mothers continue to experience NegMH even when expectations of self and child are adjusted, suggesting factors associated with the daily function of adoptive parenting put mothers at risk of NegMH, such as the experience of "extreme parenting.…”
Section: Discussionmentioning
confidence: 99%
“…Couples willing to adopt a child with problems were more likely to establish a healthy relationship with their adopted child (Figure 1), perhaps because these couples are less prone to idealize the adopted child than those not willing to adopt a child with problems. Indeed, when expectations become too high these may hinder establishment of a healthy relationship (Foli et al, 2017). Martin and Rosenhauer (2016) demonstrated that mothers adopting a child with problems had high positive adjustment and less depression and anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
“…Symbolic interactionism tells us that in this case, without a me that reflects potential difficulty, there is no I prepared to take necessary action to address whatever may arise. Research describes discrepancies between parental expectations before adoption and lived experience after adoption (Brabender & Fallon, 2013;Denby et al, 2011;Foli, Lim, & South, 2017b;Moyer & Goldberg, 2017). Evidence also indicates that some parents who adopt have more difficulty transitioning to adoptive family life than and others (Moyer & Goldberg, 2017;Tasker & Wood, 2016).…”
Section: The Transition To Parenthood and Postadoption Adjustmentmentioning
confidence: 99%